Evaluation of the physical and chemical parameters of Minas Frescal and Ricotta cheese marketed in Fortaleza, Ceará - Andrade, Ana Paula; Quirino, Michelle; Silva, Talita; Carvalho, Juliane (Revista Ciência Agronômica, 2020)
Cheeses are dairy products prepared from coagulated milk, and which, under Brazilian legislation, can be classified according to their fat and moisture content. Cheeses such as Minas Frescal and Ricotta have a high moisture content and are highly perishable. As such, chemical changes can occur and interfere with the shelf life of these products. In order to evaluate the physical and chemical parameters of Minas Frescal and Ricotta cheeses marketed in Fortaleza, Ceará, 10 samples of the products were evaluated. The variables of weight, temperature, titratable acidity, pH, moisture and fat were measured in triplicate. It was checked that the results conformed to current Brazilian legislation, and it was found that 100% of the samples had high temperature and high acidity, while the moisture content was below that established by legal standards. Some of the samples of Minas Frescal (40%) and Ricotta cheese (20%) had a low dry-extract fat index (DEF). In view of the above, greater control over production is suggested, in order to standardise the composition of the products and comply with legislative parameters, as a way of guaranteeing consumer rights and minimising health risks.